Autoimmune hepatitis and primary biliary cholangitis overlap syndrome after COVID-19 - Marlone Cunha-Silva; Eloy Vianey Carvalho de França; Raquel Dias Greca; Daniel Ferraz de Campos Mazo; Larissa Bastos Eloy da Costa; Priscilla Brito Sena de Moraes; Clauber Teles Veiga; Guilherme Rossi Assis-Mendonça; Ilka de Fátima Santana Ferreira Boin; Raquel Silveira Bello Stucchi; Tiago Sevá-Pereira (Autopsy and Case Reports, 2023)
COVID-19 is commonly associated with high serum levels of pro-inflammatory cytokines, and the post-infection status can disturb self-tolerance and trigger autoimmune responses. We are reporting a 45-year-old male who was admitted with fatigue, jaundice, elevated liver enzymes (with cholestatic pattern), and acute kidney injury two weeks after recovering from a mild SARS-CoV-2 infection. Serologies for viral hepatitis and anti-mitochondrial antibody were negative, while anti-nuclear and anti-smooth muscle antibodies were positive. There were no signs of chronic liver disease, and a magnetic resonance cholangiography showed no dilatation of biliary ducts. Histologic evaluation of the liver evidenced numerous foci of lobular necrosis without ductopenia or portal biliary reaction. Considering the autoantibody profile and histologic changes, the medical team started oral prednisone, but there was a suboptimal biochemical response in the outpatient follow-up. Two months later, a second liver biopsy was performed and revealed non-suppurative destructive chronic cholangitis, extensive areas of confluent necrosis with hepatocytes regenerating into pseudorosettes, and numerous plasma cells. According to the Paris Criteria, the patient was then diagnosed with an autoimmune hepatitis-primary biliary cholangitis overlap syndrome (AIH-PBC-OS). After adding azathioprine and ursodeoxycholic acid to the treatment, there was a satisfactory response. This is the second worldwide report of an AIH-PBC-OS triggered by COVID-19, but the first case with a negative anti-mitochondrial antibody. In this setting, histologic evaluation of the liver by an experienced pathologist is a hallmark of achieving the diagnosis and correctly treat the patient.